Development of single and multi-coil MR damper subjected to cyclic loading for structural vibration control - Daniel Cruze; Nedunchezhian Krishnaraju; Balaji Ramalingam (Advances in Civil and Architectural Engineering)
The magnetorheological (MR) damper can dissipate energy from a vibrating system with low power consumption, making it one of the most popular semi-active damping devices. This study compares single- and multi-coil dampers subjected to cyclic loading. A magnetic oil-based MR fluid is synthesized with 50% carbonyl iron and 50 % synthetic oil, resulting in maximum damping force and minimum sedimentation. A three-dimensional model of the MR damper is created using AutoCAD and is fabricated. Single- and multi-coil MR dampers with a 3000 N capacity are designed and fabricated. The MR dampers are experimentally tested in a universal testing machine with a 1000 kN capacity for various input currents from 1 to 3 A. As the current increases, the damping force also increases in both the single- and multi-coil MR dampers. The multi-coil MR damper has a maximum damping force of 2628 N at a 15 mm amplitude, and the single-coil MR damper has a maximum damping force of 1868 N. A numerical simulation of the magnetic properties of the single- and multi-coil MR dampers is conducted using the finite-element method magnetics. A spring is placed at the top of the piston pole and bottom of the piston to make the MR damper semi-active. The fabricated MR damper can be used in seismic-resistant structures and as a base isolator to protect the structure from vibrations. In addition to civil engineering, it can be used in the development of adaptive prosthetics and orthotic devices, providing dynamic support.